Isolation and Bioactivity Analysis of Ethyl Acetate Extract from Acer tegmentosum Using In Vitro Assay and On-Line Screening HPLC-ABTS+ System - Kwang Jin Lee; Na-Young Song; You Chang Oh; Won-Kyung Cho; Jin Yeul Ma (Journal of Analytical Methods in Chemistry)
The Acer tegmentosum (3 kg) was extracted using hot water, and the freeze-dried extract powder was partitioned successively using dichloromethane (DCM), ethyl acetate (EA), butyl alcohol (n-BuOH), and water. From the EA extract fraction (1.24 g), five phenolic compounds were isolated by the silica gel, octadecyl silica gel, and Sephadex LH-20 column chromatography. Based on spectroscopic methods such as 1H-NMR, 13C-NMR, and LC/MS the chemical structures of the compounds were confirmed as feniculin (1), avicularin (2), (+)-catechin (3), (−)-epicatechin (4), and 6′-O-galloyl salidroside (5). Moreover, a rapid on-line screening HPLC-ABTS+ system for individual bioactivity of the EA-soluble fraction (five phenolic compounds) was developed. The results indicated that compounds 1 and 2 were first isolated from the A. tegmentosum. The anti-inflammatory activities and on-line screening HPLC-ABTS+ assay method of these compounds in LPS-stimulated murine macrophages were rapid and efficient for the investigation of bioactivity of A. tegmentosum.